REVIEWING THE ADVANCEMENTS IN UTERINE FIBROID MANAGEMENT: A FOCUS ON MINIMALLY INVASIVE TREATMENTS (Journal of Medical & Health Sciences Review, 2025)
Objective: This review aims to summarize recent advancements in the management of uterine fibroids, emphasizing the efficacy, safety, and outcomes of minimally invasive treatments such as hysteroscopic myomectomy, laparoscopic and robotic myomectomy, uterine artery embolization (UAE), high-intensity focused ultrasound (HIFU), and radiofrequency ablation (RFA).Methods: A comprehensive literature search was performed in PubMed, Scopus, and Web of Science from 2015 to 2025 using keywords “uterine fibroid,” “leiomyoma,” “minimally invasive treatment,” and “myomectomy.” Studies focusing on procedural advancements, symptom control, fertility outcomes, and long-term reintervention rates were included. Randomized controlled trials, cohort studies, and systematic reviews were prioritized for analysis.Results: Across 85 eligible studies, minimally invasive approaches demonstrated high symptom relief (mean 75–85%) and rapid postoperative recovery, with lower complication rates compared to traditional surgery. Hysteroscopic and laparoscopic myomectomy yielded the most favorable outcomes for women desiring fertility, while UAE and RFA provided strong symptom control in non-fertility-seeking patients. Emerging technologies such as MR-guided HIFU and laparoscopic radiofrequency ablation showed promise in reducing hospitalization and preserving uterine integrity.Conclusion: Minimally invasive interventions for uterine fibroids represent a major advancement in gynecologic surgery, offering effective symptom relief, faster recovery, and preservation of fertility. The selection of modality should be individualized, guided by fibroid characteristics, reproductive goals, and available expertise. Future research should focus on long-term comparative outcomes, cost-effectiveness, and patient-reported satisfaction to optimize treatment algorithms.